STRATEGI PENGEMBANGAN USAHA PEREMPUAN PELAKU UMKM DI KOTA AMBON - Sasongko, Bin Raudha Arif Hanoeboen, Pudjihardjo, (IQTISHODUNA, 2012)
Research explores the most appropriate strategies which are made to develop women as UMKM Actor at Ambon City. The field review shows that for business development, the UMKM Actor must increase the entrepreneurship capability by emphasizing on the empowerment aspect of public economic because both are very important features for UMKM Actor at Ambon City. Research method is qualitative method. Data collection techniques involve interview, observation and documentation. The first informant is selected by purposive sampling. Next informant is selected through snowball sampling, while the final informant is based on the satiation rate of information, in wich no more variance of information is required. Data collected from the field are analyzed using Spradley Model. Domain analysis technique is the first step, and continued by taxonomy technique. Interview, observation and documentation are conducted over the artisan of pearl mollusk, fish trader and entrepreneur of fumed fish, who are mostly women. The supporting interview and documentation from related agencies at Ambon City are also considered. Research recommends the business development strategy which is expected to be the guide to the similar business development works and the empowerment effort for the women of UMKM Actor at Ambon City.